2013 Humaine Association Conference on Affective Computing and Intelligent Interaction 2013
DOI: 10.1109/acii.2013.162
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Amplitude Coupling between EEG and EDA While Experiencing Multimedia Content

Abstract: Abstract-Emotion is a dynamic process that affects social relationships and influences the mechanisms of rational thinking and decision making. The influence of emotion on reasoning has gained a lot of attention in computer science. One approach to incorporating emotions into computers is by extracting features from various physiological signals and inferring the corresponding emotions or emotional dimensions. However, physiological processes are dynamic rather than static, and physiological signals mainly int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…In the field of affective computing, much research on emotion recognition in response to multimedia content has been carried out using EEG signals, peripheral physiological signals and facial expressions [9], [11]. In the area of highlights detection, various models have involved physiological measurements of a single viewer when watching of media, such as movies [7], music excerpts [14], and sport events [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of affective computing, much research on emotion recognition in response to multimedia content has been carried out using EEG signals, peripheral physiological signals and facial expressions [9], [11]. In the area of highlights detection, various models have involved physiological measurements of a single viewer when watching of media, such as movies [7], music excerpts [14], and sport events [6].…”
Section: Introductionmentioning
confidence: 99%
“…While constructing these features we were inspired by the Appraisal Model of Emotion, as proposed by Scherer [58], which states that the activation of certain physiological components are coupled, or synchronized, when we are faced with an emotional stimulus. Also following this theory, Kroupi et al have shown coupling between the phase and amplitude of the EEG and EDA signals while the subjects are watching emotionally stimulating music videos [59]. Another example of a similar analysis is the multiple works by Williamson et al, who have shown the existence of a difference in coordination, movement, and timing of vocal and facial components between patients suffering from major depressive disorder (MDD) vs. control subjects [60], [61], winning the AVEC 2013 [62] and AVEC 2014 [63] challenges on automatic detection of MDD severity.…”
Section: Feature Constructionmentioning
confidence: 99%
“…Since physiological reactions are considered to be an important component of emotions [15], [4], their measurements provide insight into spectators' aesthetic experience elicited by particular scenes [24]. In the field of affective computing, researchers have attempted to investigate emotion recognition in responses to multimedia content using electroencephalography (EEG) signals, peripheral physiological signals and facial expressions [14], [22]. The combination of spectators' physiological signals has been proposed in [5].…”
Section: Introductionmentioning
confidence: 99%